A trnH-psbA barcode genotyping assay for the detection of common apricot (Prunus armeniaca L.) adulteration in almond (Prunus dulcis Mill.). Issue 1 (1st January 2020) - Uncu, Ayse Ozgur
ABSTRACT: Almond kernels can be mixed with apricot ( Prunus armeniaca L.) seeds while preparing certain almond-based products such as marzipan, without an identifiable alteration in the final product's sensory attributes. Consequently, apricot kernels are the most commonly utilized almond substitutes for the economic adulteration of almonds. In the present work, the trnH-psbA intergenic spacer was evaluated as a potential PCR-based authenticity marker of almond. The barcode enabled the straightforward discrimination of almond and apricot in their blends, based on diagnostic length polymorphisms between the two closely related Prunus species. The proposed assay simultaneously amplifies and distinguishes almond- and apricot-specific trnH-psbA barcode fragments from mixed samples. The barcode size of almond segregates significantly from peach as well, which is a secondary source for the economic adulteration of almond kernels. The proposed trnH-psbA genotyping assay is easy and selective for the discrimination of almond from its potential adulterants when present as admixtures.